1998
DOI: 10.1073/pnas.95.4.1812
|View full text |Cite
|
Sign up to set email alerts
|

Negative regulation of granulocytic differentiation in the myeloid precursor cell line 32Dcl3 byear-2, a mammalian homolog ofDrosophila seven-up, and a chimeric leukemogenic gene,AML1/ETO(MTG8)

Abstract: The polyomavirus enhancer binding protein 2␣B (AML1͞PEBP2␣B͞Cbfa2) plays a pivotal role in granulocyte colony-stimulating factor (G-CSF)-mediated differentiation of a myeloid progenitor cell line, 32Dc13. In this article, we report the identification of a PEBP2␣B interacting protein, Ear-2, an orphan member of the nuclear hormone receptor superfamily that directly binds to and can inhibit the function of PEBP2␣B. Ear-2 is expressed in proliferating 32Dc13 cells in presence of interleukin 3 but is down-regulate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
54
0

Year Published

1999
1999
2009
2009

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(54 citation statements)
references
References 41 publications
0
54
0
Order By: Relevance
“…32D/WT1 cells stably expressing the AML1-MTG16 fusion protein are crippled in their ability to both proliferate and differentiate into granulocytes when grown in the presence of G-CSF (Figure 1). Thus, the biological effect of AML1-MTG16 on 32D/WT1 cells partially differs from the effect of AML1-MTG8, which was shown to negatively affect only G-CSF-induced granulocyte differentiation, but not proliferation in 32D cells (Ahn et al, 1998;Kohzaki et al, 1999). AML1-MTG16 differs structurally from AML1-MTG8 in the MTG moiety.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…32D/WT1 cells stably expressing the AML1-MTG16 fusion protein are crippled in their ability to both proliferate and differentiate into granulocytes when grown in the presence of G-CSF (Figure 1). Thus, the biological effect of AML1-MTG16 on 32D/WT1 cells partially differs from the effect of AML1-MTG8, which was shown to negatively affect only G-CSF-induced granulocyte differentiation, but not proliferation in 32D cells (Ahn et al, 1998;Kohzaki et al, 1999). AML1-MTG16 differs structurally from AML1-MTG8 in the MTG moiety.…”
Section: Discussionmentioning
confidence: 99%
“…IC confirmed that AML1-MTG16 was still expressed during G-CSF treatment up to day 9 (Figure 1d, right). The growth inhibition induced by AML1-MTG16 was not among the biological effects induced by AML1-MTG8 in 32D cells (Ahn et al, 1998;Kohzaki et al, 1999), strongly suggesting that the MTG16 moiety could be responsible for this effect. , were selected for subsequent analysis.…”
Section: Aml1-mtg16 Impairs Both G-csf-induced Differentiation and Prmentioning
confidence: 99%
“…The ␣B/AML1 ¹/-embryos do not show the emergence of haematopoietic cells from the haematogenic endothelium population (T. Yokomizo & Y. Ito, manuscript in preparation). The available evidence suggests that ␣B/AML1 is also essential for terminal differentiation of myeloid progenitor cells (Tanaka et al 1995a,b;Ahn et al 1998;Kitabayashi et al 1998b).…”
Section: ␣B/aml1mentioning
confidence: 99%
“…The region between residues 1 and 49 prevents the Runt domain from interacting with either PEBP2␤ or DNA. transcription inhibition domain, TE1, 2 and 3: transcription activation elements, NLS: nuclear localization signal, NRDBn and NRDBc: negative regulatory region for DNA binding, located at N-terminal, and C-terminal sides, respectively, NRHn and NRHc: negative regulatory region for heterodimerization, located at N-terminal and C-terminal sides, respectively, Nuclear Matrix Association: the region tightly associated with nuclear matrix (Chen et al 1998), PPPY: so called PY motif to which WW-domain containing Yes associated protein (YAP) binds (Yagi et al 1999), Smads 1, 2, 3, 5: the region responsible for interaction with Smad1, Smad2, Smad3 and Smad5 (Hanai et al 1999), p300: the region responsible for interaction with p300 (Kitabayashi et al 1998a), Ear-2: the region responsible for interaction with Ear-2 (Ahn et al 1998), MAPK: two serine residues phosphorylated by MAP kinase (Tanaka et al 1996).…”
Section: Autoinhibition Of Dna Binding and Heterodimerizationmentioning
confidence: 99%
“…61,62 The ectopic expression of the AML1/ETO fusion gene product in 32Dcl3 murine myeloid precursor cells has been shown to stimulate cell proliferation without inducing morphologic terminal differentiation into mature granulocytes in response to G-CSF. 43,63,64 In addition, AML1/ETO gene expression has also been found to elevate the expression of the G-CSF receptor. 65 This upregulation depends on the CCAAT/enhancer binding protein (C/EBP) binding site, which suggests that the overproduction of G-CSF receptor is at least partly mediated by C/EBP⑀, whose expression is activated by AML1/ETO.…”
Section: Wt1mentioning
confidence: 99%